Metrological equipment for verification and calibration of non-automatic weighing instruments – axle and crane weighting instrument - Tomas Gajdosik; Lubos Kucera; Igor Gajdac; Anton Fric; Jaromir Markovic (Metrology and Measurement Systems, 2021)
The paper deals with the design of equipment for verification and calibration of axle and crane weighing instruments. In its introduction, it discusses the basic concepts of axle and crane weighing instruments, their calibration, and verification. The paper briefly describes the original technical design solution used in the calibration and verification of these weighing instruments. Subsequently, the article describes the legislative, technical and functional requirements for metrological equipment being developed. The paper presents two design solutions for handling calibration weights. In both solutions, the construction and individual functional parts of the equipment are described. Both of these solutions were designed and tested in practical measurements in the Laboratory for Testing ofWeighing Instruments of the Slovak Legal Metrology n.o. Finally, the paper presents the results of the development of a new measuring system at the University of Žilina.